Effect of Psychology Internship on Stigma of Psychiatric Disorders in Nursing Students - Saeed Vaghee; Masoud Kashani Lotfabadi; Azam Salarhaji; Nastaran Vaghei; Bibi Maryam Hashemi (Journal of Medical Education Development, 2018)
Background and Objective: Little attention has been paid to psychiatric disorder stigma and its impact on the selection of occupation of nurses in mental health centers during the mental internship courses, despite its importance in following up and treatment of this type of diseases. This study aimed to determine the effect of psychology internship on the stigma of psychiatric disorders in nursing students. Materials and Methods: This post-event study had one group and a pretest-posttest design. In total, 93 undergraduate nursing students at the fourth semesters of study, who were passing their psychology internship 1 course in Ebn'e Sina hospital in Mashhad, Iran. Subjects were selected through random cluster and quota sampling methods. Data collection tool was the opening minds stigma scale for health care providers (OMS-HC) by Kassam, filled at 3 different times, including before, on the last day, and 1 month after the psychology internship. Data analysis was performed using repeated measures ANOVA. Results: In this study, a significant difference was observed in changes among the periods of before (58.0±6.5), on the last day (55.9±5.4) and one month after (54.3±5.6) the psychology internship in terms of the total stigma score (P<0.001). Conclusion: According to the results of the study, psychology internship had positive impacts on reduced psychiatric disorder stigma in nursing students.